Perspectives for Teaching Literature: Creative use of Information Technology and New Methods in the Classroom (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explains the creative use of new methods and IT technologies in grades 5-6 of secondary schools as an effective means of increasing the effectiveness of literary education. Also, the specific features of teaching students to work on a problem, find a solution, prove their opinion, and use an effective storytelling method are discussed.